The Controversy over the Meaning of the Isim Isharah Dhalika and Hadha in the Qur'an: A Semantic Study by Toshihiko Izutsu and Its Application in the Tafsir of Al-Tanwir - Matsaini Matsaini; Moh. Abdul Kholiq Hasan; Kharis Nugroho; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2026)
This research explores the linguistic and theological controversies regarding the use of isim isharah (pointing words) dhalika and hadha in the Qur'an, especially in Surah Al-Baqarah. The phenomenon of using the word far point (dhalika) for objects that are close textually often gives rise to semantic debate. Using Toshihiko Izutsu's semantic theory which includes basic meaning, relational meaning, and weltanschauung, as well as examining Tafsir Al-Tanwir as a contemporary model of interpretation, this study aims to uncover the dimension  of honorific distance behind the choice of diction. The methodology used is qualitative-descriptive with a content analysis approach. The results of the study showed that the use of dhalika in Surah Al-Baqarah (dominance 51.4%) and hadha (11.4%). The dominance of dhalika is not just a spatial indicator, but an instrument of ta'zim (transcendence) that forms the worldview of monotheism. Tafsir Al-Tanwir implements this meaning through a rational-progressive approach, linking the authority of revelation to modern human consciousness through the concept of "meaningful distance".